Gambaran Penanaman Rasa Percaya Diri Anak Usia Dini Oleh Guru Di Lembaga PAUD - Latifah Latifah (Jurnal Family Education, 2021)
This research is motivated by the high self-confidence of early child in PAUD Adzkia III Village Korong Gadang, District Kuranji, Padang City. This is seen from the courage of children to express opinions to teachers and friends, not shy to rebuke friends if wrong, advise among others, and do not hesitate when appearing in front of the class. This condition is suspected of a relationship with the planting of confidence done by the teacher. The purpose of this study is to describe the planting of self-confidence in early childhood at PAUD Adzkia III institution from the aspect of independence, positive thinking, and courage to express the opinion made by the teacher. This research is quantitative descriptive research. The population in this study was 29 teachers. Sampling using cluster random sampling technique obtained 22 people sample from 75% population. Data collection techniques used are questionnaires, while the data collection tool using a questionnaire sheet. The data analysis technique used is the percentage formula. The result of the research shows that 1) the picture of self-confidence planting through the independent aspect given by the teacher to the child looks very good, 2) the picture of confidence planting through positive thinking aspect given by the teacher to the child looks very good, and 3) the picture the cultivation of trust through the brave aspect of expressing the opinion given by the teacher to the child looks very good. Suggestions in this study is expected to the teacher in order to maintain and increase confidence planting in school so that the child's confidence continues to increase